Desenvolvimento de um laboratório virtual e remoto para controle de um helicóptero com três graus de liberdade - Kaneko, Eduardo Hideki (2020)
This thesis presents the development of a virtual and remote laboratory (VRL) for the control of a 3 degrees of freedom (DOF) Helicopter. This is a mechanical system to study the dynamics of an aircraft with parallel propellers. The three movements of the plant are called pitch, elevation and travel, and the objective is to control the latter two. The mathematical model of the 3 DOF helicopter was determined by the virtual prototyping method. The output variables of the mathematical model are the angular positions and velocities of the movements, estimated by Tracking Loops, which use the discrete signals obtained by encoder sensors. The control variables of the mathematical model are the thrust forces, the identification of a polynomial allows to relate these forces to the voltages applied to the direct current motors equipped with fixed pitch propellers, that actuates on the plant. The VRL, in general, acts as an integrated development environment. It allows the design, construction, and monitoring of controllers, through an acquisition and control system composed of the technologies Octave, Block Diagram Coder (BDC, a software package developed in this work) and the NUCLEO-F767ZI microcontroller board, responsible for reading the sensors and driving the plant actuators. In order to validate all the work development, control experiments of tracking systems with state feedback were performed, with and without the Luenberger observer. The controllers were designed by LQR (Linear Quadratic Regulator) and entire eigenstructure assignment. These experiments were performed at the VRL and also through a traditional acquisition and control system, composed of MATLAB/Simulink and a National Instruments PCI-6602 acquisition board. The comparison and analysis of the results concluded that the VRL works properly for the development of control experiments. Moreover, the response of the controllers for the 3 DOF helicopter showed good results, validating the processes of mathematical modeling, output variables estimation and actuators identification.